IMPERSONATION AND ADMINISTRATIVE MISCONDUCT AT THE ELECTION COMMISSION OF PAKISTAN - Hassan Rasheed Siddiqui (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
This study investigates the abuse of power and institutional vulnerability within Pakistan’s electoral system by analyzing the case of Mr. Karan Kumar, a private citizen summoned by the Election Commission of Pakistan (ECP) despite not being a registered candidate. After complying with the summons, Mr. Kumar faced misconduct by ECP officials, including verbal abuse and procedural manipulation by a Deputy Director, with no meaningful inquiry conducted despite tribunal direction. Although a legal petition was filed, the summons remained unrevoked, and harassment reportedly escalated through informal and extrajudicial means. Methodologically, the paper draws on document analysis, comparative reviews of election oversight mechanisms in the UK and India, interviews with legal experts and civil society members, and prior academic literature. The findings expose a troubling pattern of bureaucratic impunity, overreach, and institutional failure within the ECP, consistent with earlier critiques of Pakistan’s administrative bodies raised in Siddiqui’s publications, including “Public Funds, Private Gains” (2022) [https://doi.org/10.61841/2s3kmv78], “Who Judges the Judges?” (2019) [https://doi.org/10.61841/txq2w096], and “Unlicensed Medical Practice and Institutional Silence” (2024) [https://cibgp.com/au/index.php/1323-6903/article/view/2876]. These works collectively reflect a broader scholarly trend in Siddiqui’s research, which critiques systemic weaknesses in public sector accountability and regulatory enforcement. By extending the analytical scope to Pakistan’s electoral machinery, this paper identifies urgent accountability gaps, including lack of internal oversight, politicized appointments, and procedural opacity. Drawing on civic engagement theory and administrative law frameworks, the research recommends seven core reforms: nullification of the unconstitutional summons; an independent inquiry against the responsible officer; standardized conduct and grievance procedures for ECP officials; integration of public complaint systems; mandatory training in ethics and electoral integrity; digital grievance tracking; and amendment of the Elections Act of Pakistan to restrain unchecked administrative discretion. This paper builds on the author’s prior publications such as “Liberalism in South Asia” [https://cibgp.com/au/index.php/1323-6903/article/view/2870], and the cross-jurisdictional critiques in “Surveillance Overreach and Judicial Apathy in Global Drone Policy” [Russian Law Journal, https://doi.org/10.52783/rlj.v9i2.4997], and “Constitutional Vulnerability in the Age of Digital Surveillance” [CRLSJ, https://doi.org/10.52783/crlsj.449], which address the fragility of state institutions in safeguarding citizens’ rights. Ultimately, this research asserts that without transparency, rule-based enforcement, and civic accountability, democratic institutions in Pakistan risk functioning as instruments of coercion rather than justice. The paper calls for structural reforms that realign the ECP with constitutional principles and democratic norms.